Simultaneous ablation of prmt-1 and prmt-5 abolishes asymmetric and symmetric arginine dimethylations in Caenorhabditis elegans. (2nd February 2017) - Hirota, Keiko; Shigekawa, Chihiro; Araoi, Sho; Sha, Liang; Inagawa, Takayuki; Kanou, Akihiko; Kako, Koichiro; Daitoku, Hiroaki; Fukamizu, Akiyoshi
Abstract : Protein arginine methyltransferases (PRMTs) catalyze the transfer of a methyl group from S -adenosylmethionine to arginine residues and are classified into two types: type I producing asymmetric dimethylarginine (ADMA) and type II producing symmetric dimethylarginine (SDMA). PRMTs have been shown to regulate many cellular processes, including signal transduction, transcriptional regulation and RNA processing. Since the loss-of-function mutation of PRMT1 and PRMT5, each of which is the predominant type I and II, respectively, causes embryonic lethality in mice, their physiological significance at the whole-body level remains largely unknown. Here, we show the morphological and functional phenotypes of single or double null alleles of prmt-1 and prmt-5 in Caenorhabditis elegans . The prmt-1;prmt-5 double mutants are viable, and exhibit short body length and small brood size compared to N2 and each of the single mutants. The liquid chromatography-tandem mass spectrometry analysis demonstrated that the levels of ADMA and SDMA were abolished in the prmt-1;prmt-5 double mutants. Both prmt-1 and prmt-5 were required for resistance to heat and oxidative stresses, whereas prmt-5 is not involved in lifespan regulation even when prmt-1 is ablated. This mutant strain would be a useful model animal for investigating the role of asymmetric and symmetric arginine dimethylation in vivo .